Workplace bullying: a form of moral disengagement - Ferreira, Priscila Fernanda Santiago (2019)
One of the phenomena of human violence at work that has attracted most attention is bullying. A manifestation of moral disengagement that, in a veiled and repetitive way, gains space and interferes in the life context of the workers involved. Moral disengagement is a practice that shows man's ability to elaborate explanations to justify antisocial acts, eliminating or minimizing the sense of guilt or reproach, typical characteristics of individuals who besiege. Fundamental is to understand that such interference is accentuated by following radical measures in the corporate world, since bullying has always been present at work as an abusive conduct, a repetitive and directed humiliation that undermines the dignity, physical and psychological health of a person or group. The study sought to contextualize theoretically the issues of moral harassment and moral disengagement, focusing on the work environment, based on the concepts of the main authors on the subject. Keywords: Violence. Job. Bullying. Moral Disengagement.